Teaching 1984 in the surveillance culture of schools. Issue 1 (8th April 2019) - Gilbert, Francis Jonathan; Pitfield, Margaret
Abstract : Purpose: This paper focuses on the affordances of and issues surrounding the teaching of George Orwell's novel 1984 (1949 ) as a set text for General Certificate of Secondary Education (GCSE) English and English Literature in an examination-obsessed and heavily surveilled school system. It considers this by focussing on the classroom practice of a beginning teacher tackling the teaching of this novel for the first time and the newly appointed university tutor who is required to assess her teaching against a prescribed set of national Teachers' Standards. Design/methodology/approach: A case study design is used, drawing on data from classroom observation, records of conversations and textual study. These data are analysed with reference to Perryman et al. 's (2018) re-evaluation of Foucault's Panopticon (1995), a concept which explains how institutions set up surveillance systems in which people's behaviour is shaped by their feelings of being watched. Findings: In the context of her practicum school the beginning teacher adopts a particular approach to language study as a vehicle for teaching the novel 1984 . This paper argues that such an approach, which finely focuses on the micro-detail of language, prevents teachers and students from seeing the big picture in Orwell's novel and is therefore contrary to the spirit of his writing. It also restricts teachers from approaching the novel in ways which draw on students' lived experiences as participants in the highly surveilled education system. Practical implications: The push for performativity in the current era of schooling ensures that, for English teachers, fear of failing to comply with imposed and implied norms contributes to a prevailing sense of unease about their subject. Thus, persistent pressures of exam preparation and inspection-readiness drive a wedge between their subject knowledge/expertise and the classroom practices prevalent in English teaching. Social implications: English teachers and teacher-educators are subject to a plethora of "guidelines" which filter through at every level of education and operate in a similar way to the totalitarian figurehead of Big Brother, Orwell's fictional dictator who dominates 1984 . This paper argues that away from Big Brother's all-seeing eye there are still, however, opportunities for those professional practices that do not fit within such parameters to be discussed, explored and shared. Originality/value: This paper offers a unique perspective on the teaching of George Orwell at the levels of school student, beginning teacher and teacher-educator. The Big Brother of this paper is not the Stalinist dictator of Orwell's dystopia, instead manifesting in many different education-related personas. This Big Brother demands compliance with his fuzzy norms (Courtney, 2016 ;Perryman et al., 2018 ), rules which are deliberately vague and shifting and if contravened have far-reaching consequences for all concerned in the teaching and learning of English.